Uma escrita sustentada pela paixão: a poesia erótica de Yêda Schmaltz - Vieira Júnior, Paulo Antônio (2014)
This study investigates the erotic poetry by Yêda Schmaltz present in the books in which the author used poetic masks in the building of her most unique lyrical voice, A alquimia dos nós (1979), Baco e Anas brasileiras (1985) and A ti, Áthis (1988). The eroticism built in these works in developed in parallel to a parody of anthological works of Western culture. A look back in time as a way to revamp how we see the subject over the contemporaneity was an important tool found in this research to read the works of such author in relation to those by artists in the past, as well as a step forward in the construction of an original discourse, commonly understood as an anachronic gesture. The update of some themes which are dear to erotic literature was recognized in the development of the analysis as a way to promote the political emancipation of women. The eroticism of literature of female authors was a phenomenon recognized mainly from the 1970‟s on, argued in the demonstrations of 1968, which aimed the promotion of freedom, especially in relation to the use of one‟s body. Thus, the construction of eroticism which develops between love lyricism and pornographic literature is noticed in the overt carnality of some works by the author, working as a paradigm against the repressive stigma attached to feminine freedom present in the midst of patriarchal societies. Such perspective was developed within the works in verse by Yêda Schmaltz revisiting the artistic and literary tradition and the transformation/transcontextualization based on the difference between such discourses. To read the Yêda Schmaltz poesy we use the teoris of Octavio Paz (2001), Georges Bataille (1988), Sarane Alexandrian (1993), Dominique Maingueneau (2010), Linda Hutcheon (1989), Théodor Adorno (2003), Affonso Romano de Sant‟Anna (1993), and Hans Magnus Enzensberger (1995/1985).